Resubmission of valuation for siphonic system (rev. 04) of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding resubmission of valuation for siphonic system (rev. 04) of BRAC University new campus project.